2015
DOI: 10.1016/j.healun.2015.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Erratic tacrolimus exposure, assessed using the standard deviation of trough blood levels, predicts chronic lung allograft dysfunction and survival

Abstract: Background: Erratic tacrolimus blood levels are associated with liver and kidney graft failure. We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 37 publications
3
38
1
2
Order By: Relevance
“…This socalled intrapatient variability (IPV) is defined as the fluctuation in Tac blood concentrations within an individual over a certain period of time during which the Tac dose is left unchanged (for an indepth review of Tac IPV please see reference [45]). A high Tac IPV is considered a risk factor for poor long-term outcomes after kidney transplantation, and similar findings have been reported after liver [46] and lung transplantation [47]. The first evidence for the clinical importance of Tac IPV was obtained by Borra et al who found that the within-patient variability in Tac is a significant risk factor for reaching a composite end point consisting of graft loss, biopsyproven chronic allograft nephropathy and 'doubling in plasma creatinine concentration in the period between 12 months posttransplantation and last follow up [48].…”
Section: Intrapatient Variabilitysupporting
confidence: 74%
“…This socalled intrapatient variability (IPV) is defined as the fluctuation in Tac blood concentrations within an individual over a certain period of time during which the Tac dose is left unchanged (for an indepth review of Tac IPV please see reference [45]). A high Tac IPV is considered a risk factor for poor long-term outcomes after kidney transplantation, and similar findings have been reported after liver [46] and lung transplantation [47]. The first evidence for the clinical importance of Tac IPV was obtained by Borra et al who found that the within-patient variability in Tac is a significant risk factor for reaching a composite end point consisting of graft loss, biopsyproven chronic allograft nephropathy and 'doubling in plasma creatinine concentration in the period between 12 months posttransplantation and last follow up [48].…”
Section: Intrapatient Variabilitysupporting
confidence: 74%
“…12,13,16,19,20,24 TA B L E 5 Demographic factors associated with CV > 30% from venipuncture in kidney subjects found a significant relationship (R 2 = 0.93) with a Passing and Bablok fit of y = 1.00x -0.23 (95% CI slope, 0.91-1.08; intercept, −0.69-0.3). However, none of the methods confirm medication ingestion with certainty.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical use of tacrolimus is further complicated by experiences of high intrapatient variability (IPV) with some patients experiencing fluctuation in trough levels even when the dose is left unchanged. [20][21][22][23][24] Lack of adherence to the prescribed immunosuppressive regimen is also associated with poor long-term outcomes. [1][2][3][4][5][6][7][8][9][10] It is increasingly clear that high tacrolimus IPV is associated with poor long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations